2017
DOI: 10.1071/sh16162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of porA pseudogene deletion among Neisseria gonorrhoeae isolates referred to the UK’s Gonococcal Resistance to Antimicrobials Surveillance Program

Abstract: porA pseudogene-negative Neisseria gonorrhoeae isolates produce false-negative results when examined by polymerase chain reaction (PCR) with porA pseudogene targets. In the present study, 533 representative gonococcal isolates received in 2011 via the Gonococcal Resistance to Antimicrobials Surveillance Program were examined to determine the prevalence of porA-negative isolates. Less than 0.4% (2/533) of isolates were found to be reproducibly negative with the porA real-time PCR but were confirmed as N. gonorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Like any molecular target, mutations of the porA gene could result in false-negative results test results. However, recent antimicrobial resistance studies have shown that porA mutants represented less than 0.4% of clinical NG isolates (Toby et al 2017). Primer sequences and assay components, originally designed by Biohelix Inc. (Quidel Corporation, San Diego, CA), are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Like any molecular target, mutations of the porA gene could result in false-negative results test results. However, recent antimicrobial resistance studies have shown that porA mutants represented less than 0.4% of clinical NG isolates (Toby et al 2017). Primer sequences and assay components, originally designed by Biohelix Inc. (Quidel Corporation, San Diego, CA), are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…All archived isolates were retrieved from -80C and inoculated on to non-selective GCVIT agar (GC agar base (Becton, Dickinson and Co, Le Pont de Claix, France) containing 1% Vitox (Oxoid, Basingstoke, UK)). Inoculated plates were incubated at 36C in 5% CO2 for 18-24 h. Growth was subcultured on to GCVIT agar plates and incubated again at 36C in 5% CO2 for 18-24 h. Identification of isolates as N. gonorrhoeae had previously been performed by real-time PCR using opa and porA targets, 10 or by MALDI-ToF.…”
Section: N Gonorrhoeae Isolatesmentioning
confidence: 99%
“…A possible justification for these discrepancies may be attributable to geographic and www.nature.com/scientificreports/ climatic variations in different regions of world. Some of the studies documented a very low prevalence of NG in cases of European population 36 while other studies reported a very high prevalence in American population 37 .…”
Section: Discussionmentioning
confidence: 99%